Sistema de control y seguimiento de carga para el transporte pesado de la compañía “Transpeque” de la ciudad de Quevedo - Serrano Quevedo, Ítalo Mecías (2016)
The transport company TRANSPEQUE of Quevedo city, does not have a geolocation system and security of access to the cargo, this entails to put at risk the product and not to efficiently take advantage of the resources that demand the transportation. In the absence of a system of satellite tracking and monitoring that performs the management and control of the transfer of products, it becomes complex to know if the distribution operations are optimal; Processes of shipment, transfer, landing, return or if the transporter truck is damaged. The lack of centralized software prevents efficient use of resources, such as vehicles that are empty in different destinations in the country, cannot be managed in a timely manner to ship new goods from different cities in which they are, not being able to do so limits To the company to obtain greater profits; or if they are damaged they cannot be given the timely assistance to move a truck mechanic and carry the necessary supply of spare parts that allow to put into operation again the vehicle. The objectives of the project are to determine the roadworthiness of the implementation of a system proposal to control the transportation of merchandise, mainly to banana ports in Ecuador, as well as to the different cities of the country; Using Open Source software. Given the lack of a control, management and monitoring system in TRANSPEQUE Transport Company, it is proposed to implement a proposal to implement the most appropriate control alternatives to manage truck and freight mobility, these alternatives to a future will be chosen with the people in charge of the Company. Research techniques will be used to collect information from the company's manager and the owners of the trucks.